The Effects of Process Writing Approach on Performance of an Overcrowded EFL Writing Class at a University in Thailand - Dokchandra, D (KnE Social Sciences, 2018)
This quasi-experimental study was carried out based on a pretest-posttest one group design with two purposes: (1) to investigate the effect of the process writing approach (PWA) on the essay writing performance of students of English in an overly large class at a Thai university, and (2) to explore the participants’ opinions towards the PWA. The participants were 55 third-year students of English purposively selected for the study. The experimental procedures for the investigation lasted 10 weeks. The data with regard to the dimension of writing performance were obtained via evaluation by two experts based on Jacobs et al.’s (1981) ESL Composition Profile of academic essays generated by the students at the beginning and end of the treatment. Data pertaining to the participants’ opinions were collected through the Process Writing Approach (PWA) questionnaire. The pre-and post-test scores were computed for mean score differences using a paired sample t-test, and descriptive statistics were used to analyze the questionnaire data. The results showed that the process writing approach had a significant effect (p<.05) on the writing performance of the students in an overly large class, and the students expressed very positive opinions towards the PWA. Implications for the use of process writing approach in an overcrowded EFL writing class and recommendations for further written expression studies were offered. Keywords: Large classes, Process Writing Approach, EFL writing